Analysis of the Implementation of Penal Mediation in the Crime of Sexual Violence Against Children by Investigators - Nurramdani, Husni (Proceedings Series on Social Sciences & Humanities, 2023)
The settlement of cases of sexual violence against children can be done through litigation, which in the process can be done through penal mediation. Penal mediation as a product of restorative justice is a means of giving the perpetrator rights granted by the investigator through his discretionary authority. However, the enforcement of justice for children as victims of sexual violence based on Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection through penal mediation with the perpetrators of criminal acts becomes a problem, both in terms of the application of penal mediation in criminal acts of sexual violence against children and the impact of the application of penal mediation. The purpose of this article is to analyze and find out the role of penal mediation and its impact on victims of sexual violence against children. The research method used by the author is to use a normative method based on books, journals, and legislation, that in this analysis the application of penal mediation in acts of sexual violence against children can be carried out based on the discretion and restorative justice efforts of the investigator as well as on the decision of the victim (in this case the family of a child victim of sexual violence) and a joint decision, without reducing the essence and integrity of child protection based on Law Number 35 of 2014. The impact of the application of penal mediation is divided into 4, namely from the side of the perpetrator of sexual violence, from the victim, the view of the community, and the regulation of legislation. This article is expected to provide knowledge and become a means to improve the integration of laws and regulations, especially on the implementation of penal mediation in criminal acts of sexual violence against children.